Antibacterial activity of garlic extract and silver Nanoparticles: an in vitro analysis - SHREYASHI M; SULAGNA D; SANKARI D; THIRUMURUGAN D; INFANT SANTHOSE B; SWAMYNATHAN G (International Journal of Pharma and Bio Sciences, 2019)
Allium sativum, commonly known as garlic has been used in traditional medicine owing to its health benefiting properties. In recent times, the invention and use of novel, efficient and natural products for use against microorganisms is of utmost importance. The antimicrobial properties of garlic (Allium sativum) reside solely on the synthesis of allicin. This compound is the key for the antimicrobial property of garlic and is produced when the cloves are squished. Silver nanoparticles have been shown to have inhibitory effects on microbes. Silver nanoparticles can be obtained by various methods, but in this study silver nitrate and sodium hydro borate was used for producing the nanoparticles of silver. This study aims to find out the antibacterial potential of silver nanoparticles and its enhancement in the presence of garlic extract. The synergistic antibacterial activity of silver nanoparticles and garlic extract were studied against two bacterial isolates such as Staphylococcus aureus and Bacillus subtilis, both of which are gram positive bacteria. Agar well diffusion method was carried out to test the inhibitory effects of garlic extract and silver nanoparticles. The results obtained were comparative and the inhibitory effect was seen to be higher when garlic extract was used along with silver nanoparticles. In this study, we conclude that the silver nanoparticles used along with garlic extract shows higher antibacterial activity and the combined effect of silver nanoparticles with garlic extract can be used for the formulation of efficient antibacterial drugs in the future. These alternate and natural forms of antibacterial drugs can be used to avoid resistance in bacteria.